APARTHEID SOUTH AFRICA’S NUCLEAR WEAPONS PROGRAMME AND ITS IMPACT ON SOUTHERN AFRICA - van Wyk, Jo-Ansie (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
Apartheid South Africa’s nuclear related activities in Southern Africa have a long history. Apart from, inter alia, the development and existence of at least six nuclear devices, South Africa operated a nuclear test site in the Kalahari Desert on the borders of Botswana, utilised uranium from Southwest Africa (now independent Namibia) as its Class C Mandate and employed a nuclear deterrent strategy in response to Soviet support for Angola and liberation movements in the region. This elicited responses from the so-called Frontline States as well as the members of the Southern African Development Community (SADCC). Therefore, the purpose of this intended contribution is to determine the extent of South Africa’s nuclear activities as well as its impact on the region. Based on archival research, the article intends to make a contribution to the study of the region, the evolution of regional integration in Southern Africa and Cold War studies in Southern Africa.